Human action a treatise on economics - Von Mises, Ludwig (Indianapolis Liberty Fund, 2007)
In the foreword to Human Action: A Treatise on Economics, Mises explains complex market phenomena as "the outcomes of countless conscious, purposive actions, choices, and preferences of individuals, each of whom was trying as best as he or she could under the circumstances to attain various wants and ends and to avoid undesired consequences." It is individual choices in response to personal subjective value judgments that ultimately determine market phenomena?supply and demand, prices, the pattern of production, and even profits and losses. Although governments may presume to set "prices," it is individuals who, by their actions and choices through competitive bidding for money, products, and services, actually determine "prices". Thus, Mises presents economics?not as a study of material goods, services, and products?but as a study of human actions. He sees the science of human action, praxeology, as a science of reason and logic, which recognizes a regularity in the sequence and interrelationships among market phenomena. Mises defends the methodology of praxeology against the criticisms of Marxists, socialists, positivists, and mathematical statisticians.
Includes bibliographical references and index.
Keywords: Economics